Transient brachial plexus injury after robot-assisted elastic intramedullary nailing of midshaft clavicle fracture: a case report and literature review - Wang, Zhongyu; Zhao, Zhiyao; Zhang, Yufu; Zhang, Xigong; Han, Xiao; Li, Yanchao; Gong, Maoqi; Huang, Qiang; Tan, Jie (Frontiers in Surgery, 2025)
BackgroundAlthough brachial plexus injury following clavicle fractures is rare, it can be a serious complication with significant implications for recovery. In this report, we present a case of midshaft clavicle fracture treated with elastic intramedullary nailing, where the patient developed brachial plexus injury symptoms two months post-surgery.Case presentationA 37-year-old woman with a middle-third clavicle fracture presented to the emergency room 5 days after a traffic accident. The patient underwent robot-assisted minimally invasive elastic intramedullary nail fixation for the left clavicle fracture with TiRobot assistance. 2 months after surgery, the patient reported numbness in all fingers of the left hand, affecting both the palmar and dorsal sides, with a pronounced impact on the thumb. Additionally, the patient was unable to move the shoulder and elbow actively (grade 1). x-ray and CT imaging revealed significant callus formation at the fracture site. Electromyography (EMG) and Doppler ultrasound all suggested left incomplete brachial plexus injury with root-level impairment. Conservative treatment, including regular physiotherapist-supervised rehabilitation, was initiated. Over time, the patient experienced gradual improvement in muscle strength and resolution of numbness. 6 months after the onset of brachial plexus injury, the elastic intramedullary nail was removed. x-ray imaging revealed notable bone remodeling with reduced callus formation at the fracture site compared to the findings observed at the onset of the brachial plexus injury. The patient reported an overall recovery of 95% compared to her condition at the time of the injury, reflecting a highly satisfactory outcome.ConclusionsThis case highlights the importance of vigilance for brachial plexus injury in patients with clavicle fractures and demonstrates the potential for successful outcomes with conservative treatment. Furthermore, it contributes to the limited body of literature regarding the rare occurrence of brachial plexus injury after elastic intramedullary nailing of clavicular fractures.